Achieving better outcomes for schizophrenia patients in Hong Kong: Strategies for improving treatment adherence. (8th February 2021) - Lo, William Tak‐Lam; Ki‐Yan Mak, Daniel; Ming‐Cheuk Wong, Michael; Chan, Oi‐Wah; Mo‐Ching Chui, Eileena; Wai‐Sau Chung, Dicky; Suk‐Han Ip, Glendy; Lau, Ka‐Shing; Lee, Che‐Kin; Mui, Jolene; Tam, Ka‐Lok; Tse, Samson; et al.
Abstract: Recent research on second‐generation long‐acting injectable antipsychotics (LAI SGAs) has proven its effectiveness in minimizing medication nonadherence problem and reducing relapses. Administered by medical professionals, making quick detection of nonadherence possible, long‐acting injectable antipsychotics (LAIs) facilitate immediate intervention and recovery process, and thus are favored by psychiatrists. Despite a higher initial cost with LAIs, the subsequent schizophrenia‐related health costs for hospitalizations and outpatients are greatly reduced. With reference to guidelines published by psychiatric associations around the globe, this article looks at scenarios in Hong Kong on the management of severe mentally ill patients with regard to the use of a host of psychosocial interventions as well as LAI SGAs as a preferable treatment. In particular, it examines the benefits of using LAI SGAs for Hong Kong patients who demonstrated high nonadherence treatment rates due to their social environment. It assesses the rationale behind the early usages of LAI SGAs, which help to provide better recovery outcomes for patients.